Novel EDC-Crosslinked Hydroxypropyl banana (Musa paradisiaca) starch as a Superdisintegrant for Enhanced Oral Delivery of Pioglitazone Hydrochloride in Orodispersible Tablets - Metta, Samyuktha; Lankalapalli, Srinivas (Indian Journal of Pharmaceutical Education and Research)
Background: Orally Disintegrating Tablets (ODTs) are gaining attention for improving patient compliance, especially in pediatric, geriatric, and dysphagic populations. Objective: This study aimed to develop and evaluate pioglitazone hydrochloride ODTs using EDC-Crosslinked Hydroxypropyl Banana starch (EDC-BS) as a novel, natural superdisintegrant. The objective was to assess the efficiency of EDC-BS in enhancing tablet disintegration and drug release compared to standard formulations containing cross povidone. Materials and Methods: EDC-BS was synthesized and characterized to confirm structural modifications and improved physicochemical properties. NMR and HRMS analysis validated effective crosslinking and hydroxyl propylation of banana starch. EDC-BS exhibited superior flowability, compressibility, and swelling capacity compared to native banana starch. Pioglitazone hydrochloride ODT formulations (F1-F10) were evaluated for thickness, hardness, friability, wetting time, disintegration, and in vitro drug release. Results: Formulations containing EDC-BS (F3 and F4) demonstrated enhanced disintegration efficiency and drug release profiles. Specifically, F3 achieved 96.36% drug release within 10 min and nearly 99.35% within 30 min, comparable to the standard formulation F9 containing crosspovidone. Furthermore, friability and hardness of F3 were within the acceptable range, confirming the mechanical stability of the tablets. Conclusion: In vitro evaluations highlighted the potential of EDC-BS as a cost-effective and biocompatible superdisintegrant, achieving results comparable to synthetic counterparts while addressing limitations such as cost and environmental concerns. This study establishes EDC-BS as a promising natural alternative for ODT formulations and provides a foundation for further exploration of its applicability in pharmaceutical development.
Keywords: Orodispersible tablets; EDC-crosslinked banana starch; Superdisintegrant; Pioglitazone hydrochloride; Drug release; Pharmaceutical formulation.